SEISMIC LOW-FREQUENCY EFFECTS IN MONITORING FLUID-SATURATED RESERVOIRS - Korneev V.A.; Daley T.M.; Silin D.B.; Goloshubin G.M. (My University, 2004)
There is a complex relationship between seismic attributes, including the frequency dependence of reflections and fluid saturation in a reservoir. Observations in both laboratory and field data indicate that reflections from a fluid-saturated layer have an increased amplitude and delayed traveltime at low frequencies, when compared with reflections from a gas-saturated layer. Comparison of laboratory-modeling results with a diffusive-viscous-theory model show that low (<5) values of the quality factor Q can explain the observations of frequency dependence. At the field scale, conventional processing of time-lapse VSP data found minimal changes in seismic response of a gas-storage reservoir when the reservoir fluid changed from gas to water. Low-frequency analysis found significant seismic-reflection-attribute variation in the range of 15-50 Hz. The field observations agree with effects seen in laboratory data and predicted by the diffusive-viscous theory. One explanation is that very low values of Q are the result of internal diffusive losses caused by fluid flow. This explanation needs further theoretical investigation. The frequency-dependent amplitude and phase-reflection properties presented in this paper can be used for detecting and monitoring fluid-saturated layers.